PENERAPAN MODEL PEMBELAJARAN ADVANCE ORGANIZER KOLABORATIF DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS VIII B SMPIT IBNUL QOYYIM MAKASSAR - Mubarok, Abdul; Abdul Karim, Bisyiri; Azhar, Muh.; Surani; Sampurno, Bambang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the implementation of the collaborative Advance Organizer learning model in improving students’ learning motivation in Islamic Religious Education subjects at class VIII B of SMPIT Ibnul Qoyyim Makassar. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection. The subjects of this study were 30 students of class VIII B. Data collection techniques included observation, documentation, and tests. The results of the study indicate that the implementation of the collaborative Advance Organizer learning model in class VIII B at SMPIT Ibnul Qoyyim Makassar was carried out effectively. The learning process became more active, interactive, and student-centered. This learning model was proven to improve students’ motivation and learning outcomes in Islamic Religious Education subjects. This can be seen from the increase in students’ learning completeness in each cycle, from 36.7% in the pre-cycle with an average score of 69, increasing to 56.7% in cycle I with an average score of 75, and reaching 100% in cycle II with an average score of 86.83. Therefore, the collaborative Advance Organizer learning model is effective in improving students’ motivation, participation, understanding, and learning outcomes.